2020
DOI: 10.3390/jcm9113418
|View full text |Cite
|
Sign up to set email alerts
|

Revision Arthroscopic Bankart Repair: A Systematic Review of Clinical Outcomes

Abstract: Although the frequency of arthroscopic revision surgery is increasing in patients with recurrent dislocation after a primary shoulder stabilization, the literature describing arthroscopic revision Bankart repair has been limited. Preferred reporting items for systematic meta-analyses guidelines were followed by utilizing PubMed, EMBASE, Scopus, and Cochrane Library databases. Keywords included shoulder dislocation, anterior shoulder instability, revision surgery, stabilization, and arthroscopic Bankart repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…Another systematic review revealed a recurrence rate of 14% to 21% after primary ACR, 27 and Murphy et al 31 reported rates of 31.2% for recurrent instability and 17% for overall revision at >10-year follow-up after primary ACR. The present study revealed a positive apprehension sign in 17.4% of patients in the revision group, which agrees with the results reported by Yon et al, 52 although various studies 2,6,17 in that systematic review excluded patients with a glenoid bone defect of >20%. In the present study, there was no dislocation, and good results were obtained.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another systematic review revealed a recurrence rate of 14% to 21% after primary ACR, 27 and Murphy et al 31 reported rates of 31.2% for recurrent instability and 17% for overall revision at >10-year follow-up after primary ACR. The present study revealed a positive apprehension sign in 17.4% of patients in the revision group, which agrees with the results reported by Yon et al, 52 although various studies 2,6,17 in that systematic review excluded patients with a glenoid bone defect of >20%. In the present study, there was no dislocation, and good results were obtained.…”
Section: Discussionsupporting
confidence: 93%
“…Yon et al 52 reviewed 14 articles and 339 patients who underwent revision ACR and reported that 15.3% of patients experienced recurrent instability, including positive apprehension signs and dislocations. Another systematic review revealed a recurrence rate of 14% to 21% after primary ACR, 27 and Murphy et al 31 reported rates of 31.2% for recurrent instability and 17% for overall revision at >10-year follow-up after primary ACR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found that revision anterior shoulder stabilization techniques such as arthroscopic, open Bankart, or bony procedures yielded satisfactory outcomes, with the lowest recurrent instability rate for patients undergoing the Latarjet procedure [ 28 ]. Another review found a complication and recurrence rate of 18.0% and 15.3%, respectively, for patients undergoing arthroscopic revision Bankart repair [ 50 ]. The authors noted that postoperative improvements are found if patients are selected carefully (ie, minimal glenoid bone loss and Hill-Sachs lesion) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is extensive literature reporting the effectiveness of revision anterior shoulder stabilization techniques, particularly open revision Bankart/Latarjet repair following failed arthroscopic Bankart procedures [ 9 , 14 , 28 , 36 ]. There has also been increasing interest in the use of an arthroscopic Bankart repair in the revision setting in mixed populations (ie, failed open or arthroscopic index procedure) [ 1 , 50 ]. However, there exists a dearth of evidence on arthroscopic revision Bankart procedures for recurrent anterior shoulder instability following a failed primary arthroscopic Bankart repair.…”
Section: Introductionmentioning
confidence: 99%
“…Yon CJ et al demonstrate that arthroscopic revision Bankart repair might lead to an improvement in clinical outcomes and reasonable satisfaction with proper patient selection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%